The relationship of self-care behaviours and online learning engagement among nursing students during the Covid-19 pandemic - Mazlinda Musa; Rohani Mamat; Hamidah Hassan; Siti Fatimah Sa’at; Syed Syarizman Abd Rahim; Abdul Rahman Ramdzan; Octovia Abdullah; Vellerina Ally Paidius; Mariana Muitaba; Ashley Melissa George (Universitas Indonesia, 2023)
The COVID-19 pandemic and the sudden switch from conventional to virtual classes allegedly raised students' risk of mental health illnesses, adversely influencing their academic engagement and learning outcomes. Nursing students in Malaysia, especially those enrolled in universities in Sabah, have traditionally been accustomed to a conventional face to-face teaching and learning approach. Due to the COVID-19 pandemic, e-learning or online classes have become one of the learning methods for university nursing students in Sabah, either while they are on campus or at home, to obtain access for educational purposes. The purpose of this study was to assess the relationship between self-care behaviours and online class engagement among the university nursing students in Sabah throughout the pandemic. This study was a quantitative descriptive cross-sectional study that used the Mindful Self-Care Scale (MSCS) and the Online Student Engagement Scale (OSE). SPSS version 26. Pearson Correlation analysis showed moderate level of positive relationship (r = 0.582, p = < 0.001, n = 120). Adequate evidence exists to show that level of self-care is positively moderately related to the online classes’ engagement behaviour among the nursing students in this study. Students should possess the self control to set goals, effectively allocate their time, and avoid procrastination.